Z-Mart Program Strategy in Increasing Mustahik Economic Independence at BAZNAS Riau Province - Silawati; Aslati; Khairunnas Jamal; Mochammad Novendri S (Lan Tabur: JURNAL EKONOMI SYARIAH, 2026)
The productive zakat-based economic empowerment program continues to be developed as an instrument for transforming mustahik from aid recipients to independent business actors. However, the effectiveness of this kind of program is not enough to measure the increase in income alone, but also from the program's ability to build sustainable economic independence. This study aims to analyze the strategy of the Z-Mart Program of BAZNAS Riau Province in increasing the economic independence of mustahik, as well as identifying achievements, obstacles, and patterns of strengthening programs at the micro business level. The research uses a qualitative approach with the type of field research. Data was collected through in-depth interviews, observations, and documentation of mustahik beneficiaries, program managers, and companions in Pekanbaru City and Kampar Regency, then analyzed thematically through the stages of reduction, categorization, and data interpretation. The results of the study show that the Z-Mart strategy is carried out through mustahik selection, productive business capital assistance, stall rebranding, and business management assistance. This program has been proven to increase stock availability, business turnover, and mustahik ability to meet basic household needs. However, the economic independence of mustahik has not been fully formed because it is still hampered by the culture of kasbon, weak financial literacy, limited assistance, and lack of business expansion. These findings confirm that the success of productive zakat is determined not only by the distribution of capital, but also by the intensity of assistance and strengthening micro business governance